CD Maps—Dynamic Profiling of CD1–CD100 Surface Expression on Human Leukocyte and Lymphocyte Subsets - Kalina, Tomas; Fišer, Karel; Pérez-Andrés, Martin; Kuzílková, Daniela; Cuenca, Marta; Bartol, Sophinus J. W.; Blanco, Elena; Engel, Pablo; van Zelm, Menno C. (Frontiers in Immunology, 2019)
CD molecules are surface molecules expressed on cells of the immune system that play key roles in immune cell-cell communication and sensing the microenvironment. These molecules are essential markers for the identification and isolation of leukocytes and lymphocyte subsets. Here, we present the results of the first phase of the CD Maps study, mapping the expression of CD1-100 (n=110) on 47 immune cell subsets from blood, thymus and tonsil using an 8-color standardized EuroFlow approach and quantification of expression. The resulting dataset included median antibody binding capacities (ABC) and percentage of positivity for all markers on all subsets and was developed into an interactive CD Maps web resource. Using the resource, we examined differentially expressed proteins between granulocyte, monocyte and dendritic cell subsets, and profiled dynamic expression of markers during thymocyte differentiation, T-cell maturation, and between functionally distinct B-cell subset clusters. The CD Maps resource will serve as a benchmark of antibody reactivities ensuring improved reproducibility of flow cytometry-based research. Moreover, it will provide a full picture of the surfaceome of human immune cells and serves as a useful platform to increase our understanding of leukocyte biology, as well as, to facilitate the identification of new biomarkers and therapeutic targets of immunological and hematological diseases.